Prison Research From the Inside: The Role of Convict Autoethnography. (April 2014) - Newbold, Greg; Ian Ross, Jeffrey; Jones, Richard S.; Richards, Stephen C.; Lenza, Michael
A perspective that has often been absent in criminal justice research is that of former prisoners. This article discusses the establishment, in 1997, of "convict criminology, " a group of scholars producing research informed by their experiences of crime and the criminal justice process; that is, either those who have served time themselves or who have operated alongside prisoners as professionals in custodial settings. It is argued that such scholars face similar dilemmas to others in terms of emotionalism, but suggests that their emotions are of a different nature. While an "insider" perspective cannot lay claim to scientific "objectivity, " the article argues that the existence of emotion does not invalidate an "insider" criminologist's views. Rather, the passion engendered by the experience of incarceration can add color, context, and contour to data collection, findings, and analysis and may therefore be regarded as an essential thread in the tapestry of criminological inquiry.